Vertical stratification of the soil seed bank in wet grasslands and its implications for restoration - Tóth Ágnes (COMMUNITY ECOLOGY, 2025)
This study aimed to examine the vertical stratification of the soil seed bank in wet grasslands, with a special emphasis on seeds in deeper soil layers that are generally not considered in seed bank studies. We studied the soil seed bank at four depths: 0–10 cm, 10–30 cm, 30–50 cm, 50–70 cm in five study sites in Central Hungary. The seedling emergence method was used to detect viable seeds. The relationship between the vertical stratification of the seed bank and species traits was studied using generalized linear mixed models. We also sampled the aboveground vegetation and applied non-metric multidimensional scaling to evaluate the species composition of the seed bank and vegetation. The species richness and the seed density of different layers were significantly different; both decreasing with increasing depth. Although most viable seeds were found in 0–10 cm depth (22,632 seeds/m 2 ), an unexpected large number of seeds germinated also from the deepest soil layer (50–70 cm; 4170 seeds/m 2 ). Species without morphological specializations for spatial seed dispersal (i.e., Allium dispersal type), lower water requirements, and heavier seeds occurred in great abundance in the deeper soil layers. The dominance of species without specialized spatial dispersal suggests that they invest more in temporal dispersal by the soil seed bank. Forbs and perennial species dominated both the seed bank and the aboveground vegetation; however, the dominant species in the seed bank did not correspond to the dominant species in the aboveground vegetation. Our results suggest that the seed bank of wet grasslands does not contain the full habitat-specific species pool despite its high seed density and species richness. The restoration of the studied wet grasslands cannot rely solely on the local seed banks.